Experimental study of heat transfer enhancement in Solar Tower Receiver Using Internal Fins - Shatnawi H.; Lim C.W.; Ismail F.B.; Aldossary A. (Tech Science Press, 2023)
Heat transfer coefficients; Reynolds number; Solar energy; Solar power generation; Tubes (components); Circular and square tubes; Friction factors; Heat Transfer enhancement; Heat transfer process; Internal fins; Longitudinal fin; Solar energy plants; Temperature decrease; Fins (heat exchange)